Development and validation of performance measures for environmentally conscious manufacturing. (1st January 2013) - Singh, Perminder Jit; Mittal, Varinder Kumar; Sangwan, Kuldip Singh
Growing awareness of environmental issues has put business and government under pressure to reduce the environmental impacts involved in the production and consumption of goods and services leading to a new paradigm of environmentally conscious manufacturing (ECM). However, because of the lack of ECM performance measures, judgements about ECM have become costs in ethical or moral terms. In this paper, 11 performance measures for environmentally conscious manufacturing have been identified based on the review of 78 research papers/articles and discussion with practitioners. A survey of 285 industries in India, using a questionnaire specifically developed for this study, has been done to validate the identified performance measures. The developed performance measures have been found to be highly reliable using Cronbach's alpha. The validity of the performance measures has been assessed through factor analysis by using SPSS 11.5 for window® statistical tool.